Off-design performance modelling of a propfan aero engine. An off-design performance evaluation of a notional engine design for future reductions in fuel consumption and emissions - Hanås, David; Winkes, Frowin (My University, 2023)
The following report covers the methodology behind creating an off-design model for an existing notional propfan engine model in NPSS. Particular attention has been given to; the creation and implementation of a custom propeller element together with the relevant performance maps, ensuring operability throughout the flight en velope, proposition of thrust ratings and their accompanying scheduling strategies as well as performing whole mission envelope simulations in NPSS in order to quickly evaluate a notional engine throughout its range of operations. From this a recom mendation for how a future propfan engine could be controlled has been given along with some observations and conclusions on SFC, bleed work and operability.
Keywords: propfan; notional engine; NPSS; aerospace; sustainable aviation; net zero; IATA 2050